Logic determined by Boolean algebras with conjugate - Kondo, Michiro; Nakamatsu, Kazumi; Abe, Jair Minoro; Gabrys, B.; Howlett, R. J.; Jain, L. C. (Springer, 2006)
We give an axiomatic system of a logic characterized by the class of Boolean algebras with conjugate, which has a close connection with the theory of rough sets, and prove that the logic is decidable.